A Cautionary Note about the Use of Estimated Homicide Data for Cross-National Research. (November 2017) - Kanis, Stefan; Messner, Steven F.; Eisner, Manuel P.; Heitmeyer, Wilhelm
A major development in criminology in recent years has been the efforts by the World Health Organization (WHO) to provide reasonably reliable estimates of homicide rates for a large number of nations. In some instances, these estimates entail adjustments of the records on homicide from vital statistics or criminal justice sources submitted by participating nations. These adjustments are designed to deal with underreporting and detected anomalies. In other instances, the estimates are generated by regression modeling. The purpose of this research note is to raise awareness among the community of homicide researchers of the nature of the WHO homicide estimates and to offer caution about their appropriate use for cross-national research.